Análise da expressão gênica das peroxirredoxinas em pacientes com deficiência de glicose-6-fosfato desidrogenase e doença falciforme por hemoglobina SC - Lopes, Karina Kirschner (2014)
Reactive oxygen species (ROS) are produced by the organism under various circumstances, such as the incomplete reduction of oxygen during cell respiration and also by exogenous factors. Have certain roles in the body, however, when in excess are harmful causing lipid peroxidation, DNA damage, cell organelles and even death. So, cells have developed antioxidant systems to maintained ROS at an appropriate level. Participating in this system the antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase and peroxiredoxins (PRDX). The latter stands out for its great abundance and reactivity with substrates, in humans six PRDX were described and are located in different cellular compartments, developing important roles in cell signaling and protecting cells from oxidative damage. In erythrocytes, this protein is so abundant that only lost in concentration for the globins, indicating a probable key role in this cell type as the erythrocytes are true targets of damage caused by ROS. However, little attention has been given to the antioxidant role of peroxiredoxins in erythrocytes and there are few studies in the literature relating to some of these proteins with erythrocyte various diseases, especially in relation to haemolytic anemia, which are part dehydrogenase deficiency Glucose-6-phosphate (G6PD) deficiency whose production of NADPH appears to interfere with the catalytic cycle of peroxiredoxins, however the relationship of these proteins in G6PD deficiency and SC hemoglobinopathy has not been explored. Literature data show that the erythrocytes in patients with sickle cell disease are under constant stress, in the case of individuals with SC hemoglobinopathy seems to be a greater rate of autoxidation of hemoglobin due to instability of the hemoglobin in this disease, leading to increased ROS. Then, this study evaluated the role of PRDXs in reticulocyte of patients with diseases described above, compared with reticulocytes of healthy individuals, using real-time PCR and Western blot. The results showed that no significantly statistical difference between the gene expression of PRDX in control and in patients in the two diseases studied. As for protein expression apparently there was also no significant difference. However, when assessing the redox profile at the major PRDX found in erythrocytes, PRDX 2, along with PRDX 1, we found that these patients were more oxidized state in patients than in controls. This suggests that there is a deficiency in the recycling of these proteins due to low activity of thioredoxin reductase, also due to increased ROS in these patients. And as patients do not present a severe hemolytic anemia there may be an increased expression and/or activity of other antioxidant proteins such as glutathione peroxidase and catalase.